2016
DOI: 10.1016/j.jnutbio.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil prevents benzo(a)pyrene [B(a)P]-induced colon carcinogenesis through altered B(a)P metabolism and decreased oxidative damage in ApcMin mouse model

Abstract: Colon cancer ranks third in cancer related mortalities in the United States. Many studies have investigated factors that contribute to colon cancer in which dietary and environmental factors have been shown to play an integral role in the etiology of this disease. Specifically, human dietary intake of environmental carcinogens such as polycyclic aromatic hydrocarbons (PAHs) has generated interest in looking at how it exerts its effects in gastrointestinal carcinogenesis. Therefore, the objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 81 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…130 In addition, EVOOP, including phenolic alcohols, lignans and secoiridoids, are thought to be, in part, responsible for EVOO reported anti-carcinogenic effects. 131 EVOOP have been shown to influence carcinogenesis and tumor development at various levels: [132][133][134] by exerting antioxidant activities, 135,136 by modulating detoxification enzyme systems, 137 and the immune system, 138 by reacting with activated carcinogens and mutagens, 139,140 and by exerting actions on proteins controlling cell cycle progression, 122,141,142 and gene expression. 143,144 The ability of EVOO to inhibit colon cancer development has been demonstrated in large intestinal cancer cell models, 122,144,145 in animals 140,146 and in humans.…”
Section: Anti-carcinogenic Effect At the Intestinal Levelmentioning
confidence: 99%
“…130 In addition, EVOOP, including phenolic alcohols, lignans and secoiridoids, are thought to be, in part, responsible for EVOO reported anti-carcinogenic effects. 131 EVOOP have been shown to influence carcinogenesis and tumor development at various levels: [132][133][134] by exerting antioxidant activities, 135,136 by modulating detoxification enzyme systems, 137 and the immune system, 138 by reacting with activated carcinogens and mutagens, 139,140 and by exerting actions on proteins controlling cell cycle progression, 122,141,142 and gene expression. 143,144 The ability of EVOO to inhibit colon cancer development has been demonstrated in large intestinal cancer cell models, 122,144,145 in animals 140,146 and in humans.…”
Section: Anti-carcinogenic Effect At the Intestinal Levelmentioning
confidence: 99%
“…Though there have been many encapsulating agents available, none of them would be proper for controlling the therapeutics once it is co-loaded with the NIR dyes. [11] Recent report suggests that Adv bio-resorbable extra virgin olive oil (EVO) has anticancer effects owing to their oleocanthal components, [12] thus we explored EVO based NEMSn to encapsulate IR-780 dye along with chemotherapy agent, doxorubicin (DOX) stabilized by Tween-20, and the hyaluronic acid (HA) to impart both thermal and chemo effects on the cancer cells. Nanoemulsions (NEMSn) are the nano version of ordinary micro emulsions, which contains oily and watery part, stabilized by a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown the growth of breast, prostate, colon and lung cancer cells in culture were successfully and selectively inhibited by pomegranate (Punica granatum) extracts [20] . Olive oil phenols as chemopreventive and therapeutic effects against cancer has been reviewed [21,22] and shown that olive oil prevented experimentally induced colon cancer in a mouse model [23] .…”
Section: Introductionmentioning
confidence: 99%